2019
DOI: 10.1007/s00405-019-05494-6
|View full text |Cite
|
Sign up to set email alerts
|

Vocal fold fixation due to proximal stenosis progression complicating idiopathic subglottic stenosis

Abstract: Purpose This study examined the incidence and risk factors for vocal fold fixation due to proximal progression of idiopathic subglottic stenosis (ISS) over the course of serial treatments. Methods Records of 22 consecutive patients with ISS treated between 2004 and 2016 were retrospectively reviewed. Patient, stenosis, and treatment details were recorded. Cox regression was used to identify independent predictors of vocal fold fixation. Results All patients were female and mean age at diagnosis was 46 ± 7 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 27 publications
0
10
2
Order By: Relevance
“…To date, only one investigation has assessed the development of glottic stenosis during the management of iSGS. Nouraei et al identified vocal fold fixation due to proximal migration of subglottic scar in 32% of a cohort of iSGS patients ( n = 22), with nearly a third of these cases resulting in glottic airway compromise and 2 requiring additional surgical management (cricotracheal resection, CTR) 8 . This rate, which is significantly higher than what is reported in our cohort, was attributed to the use of coblation and potassium titanyl phosphate lasers.…”
Section: Discussioncontrasting
confidence: 58%
See 4 more Smart Citations
“…To date, only one investigation has assessed the development of glottic stenosis during the management of iSGS. Nouraei et al identified vocal fold fixation due to proximal migration of subglottic scar in 32% of a cohort of iSGS patients ( n = 22), with nearly a third of these cases resulting in glottic airway compromise and 2 requiring additional surgical management (cricotracheal resection, CTR) 8 . This rate, which is significantly higher than what is reported in our cohort, was attributed to the use of coblation and potassium titanyl phosphate lasers.…”
Section: Discussioncontrasting
confidence: 58%
“…This increased use of the laser which is transmitted between the glottis through a rigid laryngoscope in theory comes with an increased risk of thermal injury to the glottis. Aside from breathing symptoms that come with glottic stenosis, the involvement of the cricoarytenoid joint causing decreased mobility of the vocal folds is a feared condition in airway surgery given the significant complexity in management and the associated impact on voice and swallowing function 8,15 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations